2021
DOI: 10.3390/jpm11060453
|View full text |Cite
|
Sign up to set email alerts
|

Individual Resonant Frequencies at Low-Gamma Range and Cognitive Processing Speed

Abstract: Brain electrophysiological activity within the low gamma frequencies (30–80 Hz) has been proposed to reflect information encoding and transfer processes. The 40-Hz auditory steady-state response (40-Hz ASSR) is frequently discussed in relation to changed cognitive processing in neuropsychiatric disorders. However, the relationship between ASSRs and cognitive functioning still remains unclear. Most of the studies assessed the single frequency ASSR, while the individual resonance frequency in the gamma range (30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 64 publications
(108 reference statements)
2
10
0
Order By: Relevance
“…The baseline correction of the signal was performed by dividing the signal during the stimulation by the signal during the baseline averaged from −500 to −150 ms for each frequency. In accordance with previous studies utilizing chirps and classical gamma-range auditory steady-state responses, a clear fronto-central distribution of the response was observed [ 15 , 24 ]. For further evaluation, the PLIs and ERSPs at frequencies spanning 30–60 Hz were averaged for the fronto-central (Fz, Cz, FCz, C1, C2, F1, F2, FC1, and FC2) region where responses were most pronounced.…”
Section: Methodssupporting
confidence: 91%
See 3 more Smart Citations
“…The baseline correction of the signal was performed by dividing the signal during the stimulation by the signal during the baseline averaged from −500 to −150 ms for each frequency. In accordance with previous studies utilizing chirps and classical gamma-range auditory steady-state responses, a clear fronto-central distribution of the response was observed [ 15 , 24 ]. For further evaluation, the PLIs and ERSPs at frequencies spanning 30–60 Hz were averaged for the fronto-central (Fz, Cz, FCz, C1, C2, F1, F2, FC1, and FC2) region where responses were most pronounced.…”
Section: Methodssupporting
confidence: 91%
“…The sounds were similar to previously used [ 24 ] click-based chirps. Stimulus train was created of single white-noise bursts spaced with changing inter-click periods to cover a range from 30 to 60 Hz in a descending order.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that, when assessing ASSR with 40 Hz and IGF, gamma activity was associated with performance speed in both complex cognitive tasks, i.e., tapping planning and problem solving. However, in the individualized approach with IGF, the observed associations were stronger than with 40 Hz stimulation, and the associations mainly reflected individual differences in higher-order cognitive processing [2].…”
Section: Eeg Related Researchmentioning
confidence: 72%